External heating garments used post-warm-up improve upper body power and elite sprint swimming performance - Wilkins, E. L.; Havenith, G. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
The aim of this study was to determine the effects of using an electrical heating garment during a 30-min recovery period after a standardized swimming warm-up on subsequent swimming performance and upper body power output. On two occasions, eight male and four female elite competitive swimmers completed a standardized swimming warm-up, followed by a 30-min passive recovery period before completing maximal plyometric press-ups and a 50-m freestyle swim. Plyometric press-ups determined starting strength, peak force and peak concentric power. During the recovery period, participants wore tracksuit bottoms and (1) a standard tracksuit top (CON) or (2) jacket with integrated electric heating elements (HEAT). The overall results demonstrated a trend of a relevant (>0.4%) improvement in the 50-m freestyle performance of 0.83% (p = 0.06) in HEAT versus CON. In male participants, performance in the 50-m freestyle significantly improved by 1.01% (CON 25.18 ± 0.5 s vs HEAT 24.93 ± 0.4 s; p < 0.05), whereas female participants only showed a trend for an improvement of 0.38% (29.18 ± 0.5 s vs 29.03 ± 1.0 s; p = 0.09), in HEAT compared with CON, although statistical power for the latter test was low. Male participants` starting strength, peak force and peak concentric power were 16.5 ± 13%, 18.1 ± 21% and 16.2 ± 21% greater, respectively, in HEAT compared with CON (all p < 0.01). In conclusion, external heating of the upper body between completion of the warm-up and performance through the utilization of an electrically heated jacket improves plyometric press-up power output and force production, as well as sprint swimming performance in males. This provides justification for future enhancement opportunities in sporting performance through the utilization of external heating systems. Optimization of the heating system for specific sports is required.